Design of marine and offshore structures - Murthy, T. K. S.; Alaez, J. A.; International Conference on Computer Aided Design, Manufacture and Operation in the Marine and Offshore Industries (4th : 1992 : Madrid, Spain) (Southampton : CMP, 1992)
07